Severe tongue laceration repair in a polo pony: a case report - Awang Kamaludin, Dayang Norhaizum; Mohd Adzahan, Noraniza; Khairuddin, Nurul Hayah; Rais, Mohamad Naguib; Roslim, Noorashimah; Ahmad Affandi, Syahirah; Abdullah, Abraham Gabriel; J., Muhammad Fairuz (2015)
The tongue of a horse is a very muscular structure and highly mobile located on the floor of the oral cavity. Injuries involving the tongue are mostly due to lacerations caused by damage from bits or restraining equipment such as chifney. Most lacerations can heal without suturing, however in severe cases that involve body of the tongue are best managed surgically. A polo pony was referred to University Veterinary Hospital (UVH) with a complaint of bloody mouth and observed blood-stained feed. The groom was unsure of the actual cause of the injury, but suspected it can be caused by a bit. Full thickness laceration of the body of the tongue was examined, and there were visible blood vessels and connecting tissues observed. Detomidine infusion was used to sedate the pony and maintained throughout the tongue repair. The oral cavity and the tongue was extensively cleansed using water and very diluted hibiscrub prior repair. Tongue was sutured, and the groom was advised to clean and wash the oral cavity using diluted hibiscrub after every feeding. Antibiotic and non-steroidal anti-inflammatory drugs (NSAIDs) were prescribed and adviced for post tongue repair. In conclusion, tongue is a highly mobile structure and risk of wound dehiscence can occur unless care is taken to align the tongue correctly and to repair the injury correctly. Surgical repair of the tongue is indicated when body of the tongue is severely severed.